Structure, Texture and Catalytic Properties of CuO/FeO and CuFeO - A.M. Youssef; G.E. Badr; Th. El-Nabarawy (Adsorption Science & Technology, 1996)
CuO/Fe 2 O 3 (1:1) was prepared by co-precipitation. Six thermal products (I–VI) were obtained by calcination in the temperature range 300–800°C. The structures of I–VI were determined from XRD patterns and they were also identified from electrical conductivity measurements in the temperature range 313–523 K. The textural properties were determined from nitrogen adsorption at 77 K and the acidities of the thermal product were measured by pyridine chemisorption at 423 K. The decomposition of H 2 O 2 over the catalysts I–VI was followed in the temperature range 303–323 K. Conversion of 2-propanol was investigated at 523 K. Calcination of CuO/Fe 2 O 3 at 600°C resulted in partial transformation to CuFe 2 O 4 , this transformation predominating at 700°C and being complete at 800°C. Two mechanisms of electrical conduction are involved for catalysts calcined at 600–800°C depending on the temperature at which σ is measured. The surface area decreases and the average pore radius increases with increasing calcination temperature due to sintering and spinel formation. A mechanism is suggested for H 2 O 2 decomposition and the activity and selectivity of the catalysts towards the conversion of 2-propanol are discussed.